Structural modifications toward improved lead-203/lead-212 peptide-based image-guided alpha-particle radiopharmaceutical therapies for neuroendocrine tumors. - Lee, Dongyoul; Li, Mengshi; Liu, Dijie; Baumhover, Nicholas J.; Sagastume, Edwin A.; Marks, Brenna M.; Rastogi, Prerna; Pigge, F. Christopher; Menda, Yusuf; Johnson, Frances L.; Schultz, Michael K. (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
Purpose: The lead-203 (203Pb)/lead-212 (212Pb) elementally identical radionuclide pair has gained significant interest in the field of image-guided targeted alpha-particle therapy for cancer. Emerging evidence suggests that 212Pb-labeled peptide-based radiopharmaceuticals targeting somatostatin receptor subtype 2 (SSTR2) may provide improved effectiveness compared to beta-particle-based therapies for neuroendocrine tumors (NETs). This study aims to improve the performance of SSTR2-targeted radionuclide imaging and therapy through structural modifications to Tyr3-octreotide (TOC)-based radiopharmaceuticals. Methods: New SSTR2-targeted peptides were designed and synthesized with the goal of optimizing the incorporation of Pb isotopes through the use of a modified cyclization technique; the introduction of a Pb-specific chelator (PSC); and the insertion of polyethylene glycol (PEG) linkers. The binding affinity of the peptides and the cellular uptake of 203Pb-labeled peptides were evaluated using pancreatic AR42J (SSTR2+) tumor cells and the biodistribution and imaging of the 203Pb-labeled peptides were assessed in an AR42J tumor xenograft mouse model. A lead peptide was identified (i.e., PSC-PEG2-TOC), which was then further evaluated for efficacy in 212Pb therapy studies. Results: The lead radiopeptide drug conjugate (RPDC) — [203Pb]Pb-PSC-PEG2-TOC — significantly improved the tumor-targeting properties, including receptor binding and tumor accumulation and retention as compared to [203Pb]Pb-DOTA0-Tyr3-octreotide (DOTATOC). Additionally, the modified RPDC exhibited faster renal clearance than the DOTATOC counterpart. These advantageous characteristics of [212Pb]Pb-PSC-PEG2-TOC resulted in a dose-dependent therapeutic effect with minimal signs of toxicity in the AR42J xenograft model. Fractionated administrations of 3.7 MBq [212Pb]Pb-PSC-PEG2-TOC over three doses further improved anti-tumor effectiveness, resulting in 80% survival (70% complete response) over 120 days in the mouse model. Conclusion: Structural modifications to chelator and linker compositions improved tumor targeting and pharmacokinetics (PK) of 203/212Pb peptide-based radiopharmaceuticals for NET theranostics. These findings suggest that PSC-PEG2-TOC is a promising candidate for Pb-based targeted radionuclide therapy for NETs and other types of cancers that express SSTR2.